War crimes tribunals in Bangladesh: a socio-political and legal impact analysis ICSR - Jalil, Md. Abdul (Macrothink Institute, USA, 2012)
Till 1970, Bangladesh was still an underdog state of West Pakistan and the people of the future “Bangladesh” were gravely displeased with the Government of Pakistan that governed “Bangladesh” for various reasons of bad governance and hypocritical administration. As a result, “Bangladeshi” people declared an independence movement in March 1971 to relieve themselves from the yoke of gross incompetent governance of the ruling Government. The Freedom Fighters of Bangladesh fought a liberation fight against the Pakistani Army for 9 months after which they were ultimately and decisively victorious on 16 December 1971 and emerged as an independent country named as ‘Bangladesh’. After the independence of Bangladesh, Sheikh Mujibur Rahman, the first Prime Minister of Bangladesh, enacted the International War Crimes (Tribunals) Act 1973 (IWCTA 1973) to punish the war criminals during the 9 months of liberation movement. The object of this paper is to critically analyze the provisions in the IWCTA 1973 in light of the international war crime laws find its deadly flaws.